Diakonia Transformatif Dalam Gereja HKBP: Telaah Teologis dan Kontekstual: Transformative Diakonia in the HKBP Church: A Theological and Contextual Study - Siregar, Casandro; Siagian, Riris Johanna (MURAI: Jurnal Papua Teologi Konstekstual, 2025)
This article aims to examine in depth the understanding and praxis of transformative diakonia in the Huria Kristen Batak Protestan (HKBP) Church with five main focuses, namely the theological basis of diakonia, diakonia in HKBP tradition and understanding, the concept of transformative diakonia, contextual analysis in Batak and Indonesian society, and practical implications for the church today. The study begins with an exploration of the theological foundation of diakonia which is rooted in God's love and Christ's mission to bring liberation to humanity as a whole. Next, the paper traces the historical development and forms of diaconal ministry within HKBP and its challenges in responding to the needs of the times. The concept of transformative diakonia is analyzed as a form of service that does not stop at mercy, but encourages structural change and social justice. Through a contextual approach, this article maps the socio-cultural dynamics of the Batak community and the condition of Indonesia which is the actual field of church service. Finally, this article emphasizes the importance of renewing the paradigm of diakonia within HKBP to be more relevant, participatory, and transformative for the wider community